Education, Altitude, and Humidity Can Interactively Explain Spatial Discrepancy and Predict Short Stature in 213,795 Chinese School Children - Ma, Jia; Zhang, Zhixin; Niu, Wenquan; Chen, Jie; Guo, Sihui; Liu, Shufang; Dong, Yanhui; Yang, Zhaogeng; Wang, Wenlai; Song, Ci; Ma, Jun; Pei, Tao (Frontiers in Pediatrics, 2019)
Backgrounds and Objectives: The north–south height distinctions in Chinese children suggest that some geographical–climatic factors could determine height variation of short stature. In a national health survey, we aimed to explore the spatial distribution of short stature on city scales, and detect its socio-economic and geographical–climatic factors. Methods: Data on the prevalence of short stature were obtained from a 2014 (CNSSCH) cross-sectional survey of China. In total, 213,795 Han Chinese students aged 7–18 years, from 106 cities across 30 provinces, were included. Both China and World Health Organization (WHO) growth references were adopted to define short stature. Results: A spatial clustering was apparent in the distribution of short stature. After multivariable adjustment, altitude and humidity significantly increased the risk of high prevalence in short stature, according to the WHO (odds ratio [OR] = 1.61 and 1.26, 95% confidence interval [CI]: 1.20–2.17 and 1.03–1.54) and China (OR = 1.54 and 1.26; 95% CI: 1.15–2.05 and 1.02–1.55) growth references. Additionally, education significantly decreased the risk of high prevalence in short stature according to the WHO (OR = 0.40 and 95% CI: 0.22–0.74) and China (OR = 0.42 and 1.26, 95% CI: 0.22–0.77) growth references. Combining both altitude >400 m and education <9 years, as well as education <9 years and humidity >70%, received the largest effect-size estimate, and significance retained after multivariable adjustment. Conclusions: Our findings indicate that high altitude and humidity increased the risk of high prevalence in short stature, high education was associated with low prevalence. Additionally, we observed possible interactions between education and altitude/humidity. Further validations are necessary.